Experimental studies of the uncontrolled shift of the bulldozer - I. P. Troyanovskaya; A. O. Zhakov (Вестник СибАДИ, 2022)
Introduction. External forces from the working body of a road-building machine sometimes lead to its uncontrolled deviation from a given trajectory when performing a technological cycle. In this case, there is a clear dependence of the magnitude of the shift force on its direction. The purpose of experimental studies was to determine the values of the limiting shift force for its various directions.Materials and methods. The experimental tests were carried out on the example of a 10-ton caterpillar bulldozer manufactured by the Chelyabinsk Tractor Plant. The shift was carried out by the action of an external force applied to the edge of the dump in various directions. The external force was recorded on an oscillogram.Results. The shift began with an external force equal to the adhesion limit, provided that the line of action of the external force passed through the center of pressure. The shift begins at much lower values of the external force when the line of action of the external force deviates from the center of pressure. The result of the experiment was the construction of a hodograph of the limiting shift force.Conclusion. The nature of the change in the external force during translational and rotational shear was fundamentally different. It has been experimentally confirmed that the more the direction of the shear force deviates from the center of pressure of the machine, the smaller the value of the external force can lead to an uncontrolled shear.